Persepsi UMKM Terhadap Risiko Penipuan QRIS dan Strategi Pengamanannya - Farrel Daffa Kamal; Putra Adi Wijaya; Risma Anggreani (CV. Multi Kreasi Media, 2025)
QRIS (Quick Response Code Indonesian Standard) has become a popular digital payment method among MSMEs due to its ease and speed of transactions. However, the increasing use of QRIS is also accompanied by the risk of digital fraud, such as fake QRIS, phishing links, and code substitution by irresponsible parties. This study aims to understand MSMEs' perceptions of the risk of QRIS fraud and the security strategies they implement. The study used a qualitative phenomenological approach through in-depth interviews, observation, and documentation of culinary MSMEs in Tangerang and Bogor. The results show that MSMEs' risk perceptions vary according to experience and digital literacy, and the level of risk awareness is related to the implementation of security strategies, ranging from QR code verification, the use of secure devices, internal training, to the use of additional security features such as OTP and encryption. Consistently implemented security strategies are perceived to be able to reduce potential risk of loss, increase security, and maintain customer trust. These findings confirm the close relationship between risk perception and mitigation measures and provide practical recommendations to support the safe and sustainable use of QRIS for MSMEs.